The time optimal path-planning of mobile robots motion respecting the time cost of rotation - Škrabánek Pavel; Mariška Martin; Doležel Petr (IEEE (Institute of Electrical and Electronics Engineers), 2015)
The paper describes the time optimal path-planning method designed for differential wheeled mobile robots operating on flat ground. The robots are used as support teaching tool by the path-planning problematic exercising. Whereas the exercise is designed for students without any prior knowledge about the path-planning, the graph version of the A* algorithm was chosen as the appropriate algorithm for the problematic introduction. The students are supposed to exercise the path-planning using the evaluation functions of various difficulties. The most complex of them is the evaluation function reflecting both the transportation time and the time required for a robot rotation. Its mathematical formulation is described in the paper and its functionality is shown in three case studies where the shortest time-path between two locations in a labyrinth is required to be found.
Plánování pohybu s pohledu optimalizace času se zohledněním časové náročnosti rotace
Keywords: mobile robot, path-planning, A* algorithm; mobilní robot, plánování pohybu, algoritmus A*